Engineering Functional Vasculature in Decellularized Lungs Depends on Comprehensive Endothelial Cell Tropism - Akinnola, Ifeolu; Rossi, Daniel R.; Meyer, Carolyn; Lindsey, Ashley; Haase, Douglas R.; Fogas, Samuel; Ehrhardt, Michael J.; Blue, Rachel E.; Price, Andrew. P.; Johnson, Max; Alvarez, Diego F.; Taylor, Doris A.; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Tissue engineering using decellularized whole lungs as matrix scaffolds began as a promise for creating autologous transplantable lungs for patients with end-stage lung disease and can also be used to study strategies for lung regeneration. Vascularization remains a critical component for all solid organ bioengineering, yet there has been limited success in generating functional re-endothelialization of most pulmonary vascular segments. We evaluated recellularization of the blood vessel conduits of acellular mouse scaffolds with highly proliferating, rat pulmonary microvascular endothelial progenitor cells (RMEPCs), pulmonary arterial endothelial cells (PAECs) or microvascular endothelial cells (MVECs). After eight days of pulsatile perfusion, histological analysis showed that PAECs and MVECs possessed selective tropism for larger vessels or microvasculature, respectively. In contrast, RMEPCs lacked site preference and repopulated all vascular segments. RMEPC-derived endothelium exhibited thrombomodulin activity, expression of junctional genes, ability to synthesize endothelial signaling molecules, and formation of a restrictive barrier. The RMEPC phenotype described here could be useful for identifying endothelial progenitors suitable for efficient vascular organ and tissue engineering, regeneration and repair.